Optically stimulated luminescence characteristics of BeO nanoparticles synthesized by sol-gel method. (November 2018) - Altunal, V.; Yegingil, Z.; Tuken, T.; Depci, T.; Ozdemir, A.; Guckan, V.; Nur, N.; Kurt, K.; Bulur, E.
Abstract: Optically Stimulated Luminescence (OSL) properties of the sol-gel synthesized nano-powders of Beryllium Oxide (BeO) were investigated. Luminescence properties of BeO nanoparticles are dependent on the crystal structure, particle size, and morphology and therefore strongly dependent on the way of synthesis, thus the preparation was modified to enhance the OSL signal from the material. Structural, thermal and morphological properties of BeO in nanopowder and pellet forms were studied using X-Ray Diffraction (XRD), Fourier Transform Infrared Microscopy (FTIR), Simultaneous Thermal Analysis STA (Thermo Gravimetric Analysis (TGA)/Differential Scanning Calorimetry (DSC)) and Scanning Electronic Microscopy (SEM) techniques. XRD and STA analysis suggested an enhancement in crystallinity and thermal stability of the BeO with increasing sintering temperature. OSL dosimetric properties of the pellets prepared by pressing the synthesized powders were investigated in detail. Thermal stability of the signal as determined with a pulse heating experiment has shown that the OSL signal was stable up to depleted at around 300 °C, suggesting the suitability for dosimetric purposes. Dose response of OSL signals was observed to be linear in the dose range 0.1–100 Gy. The minimum detectable dose limit was estimated at around 100 μGy. Replicated measurements of the samples irradiated with the same dose indicated a good repeatability. Fading properties of the OSL signals were also studied up to 1 month. OSL signals of BeO pellets were decreased by approximately 11% at the end of 7 days and by about 17% at the end of 30 days when compared with the first readout. Highlights: BeO nano-phosphors synthesis using Sol-Gel method. Structural characterisation of BeO nano-phosphors. Investigation of optically stimulated properties of BeO pellets. Dosimetric characteristics of BeO.